Preparation method of electroluminescent quantum dot surface modification material
Patent Information
- Application Number
- CN202610850309.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-12
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]然而,现有方法中,RAFT配体通常以单锚定基团连接量子点,结合强度有限,且后续聚合步骤复杂,常常需要多次分离纯化,不利于规模化制备,同时,多数方法仅关注单一载流子(空穴或电子)的传输优化,忽视了载流子平衡注入的重要性,且缺乏对量子点长期稳定性的有效保护
1、该电致发光量子点表面修饰材料的制备方法,通过采用硫辛酸双硫环双锚定结构与RAFT活性端基结合的LA-RAFT功能配体,并对量子点进行配体交换的方式,实现量子点表面功能化配体高稳固接枝,双锚定基团可大幅增强配体与量子点表面的结合强度,有效避免传统单齿配体易脱落、修饰层不稳定的问题,为后续聚合提供均匀、牢固的反应位点。
Smart Images

Figure CN122897953A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of quantum dot optoelectronic materials technology, specifically to a method for preparing electroluminescent quantum dot surface modification materials. Background Technology
[0002] Quantum dots have shown application potential in electroluminescent devices (such as quantum dot light-emitting diodes, QLEDs) due to their unique optical properties, such as size-tunable emission wavelength, strong fluorescence quantum yield, and narrow emission peak width. However, quantum dots, especially those synthesized in the oil phase, are usually coated with long-chain organic ligands (such as oleic acid and oleylamine). These ligands have good insulation properties, which is not conducive to the effective injection and transport of charge carriers. In addition, the binding of traditional monodentate ligands to the surface of quantum dots is weak, and they are prone to detachment during device fabrication and use, leading to quantum dot aggregation, an increase in surface defect states, and consequently, a decrease in device luminous efficiency and a deterioration in operating stability.
[0003] To overcome the above problems, researchers have developed a variety of quantum dot surface modification strategies, such as ligand exchange, coating with inorganic shells, and grafting polymer brushes. Among them, grafting functional polymer brushes onto the surface of quantum dots through reversible addition-fragmentation chain transfer (RAFT) polymerization has attracted attention because it enables precise control over the molecular weight, structure, and thickness of the polymer.
[0004] However, in existing methods, RAFT ligands are usually linked to quantum dots with a single anchoring group, resulting in limited binding strength. Furthermore, the subsequent polymerization steps are complex and often require multiple separation and purification steps, which is not conducive to large-scale preparation. At the same time, most methods only focus on optimizing the transport of a single charge carrier (hole or electron), neglecting the importance of balanced charge carrier injection, and lack effective protection for the long-term stability of quantum dots. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing electroluminescent quantum dot surface modification materials to solve the problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing an electroluminescent quantum dot surface modification material includes the following steps: S1. Synthesis of bifunctional ligands with bi-anchored-reversible addition-fragmentation chain transfer: A bifunctional ligand containing a disulfide ring anchoring group of lipoic acid and a RAFT polymerization active end group was prepared by esterification reaction of lipoic acid with a carboxyl-containing RAFT reagent, denoted as LA-RAFT. S2, Ligand exchange and RAFT functionalization of quantum dot surface: The quantum dots synthesized in oil phase are dispersed in an organic solvent, and the LA-RAFT ligands obtained in step S1 are added to carry out a ligand exchange reaction. After centrifugation and washing to remove unreacted ligands, quantum dots with LA-RAFT grafted on the surface are obtained, denoted as QD-RAFT. S3. Controlled polymerization grafting of hole transport blocks: The QD-RAFT obtained in step S2 is dispersed in a degassed solvent, hole transport monomers and free radical initiators are added, and RAFT polymerization reaction is carried out to graft hole transport polymer brushes onto the surface of quantum dots to obtain QD-polymer brushes. S4. In-situ copolymerization to introduce electron transport units and crosslinkable silane groups: Electron transport monomers and crosslinkable silane monomers are directly added to the reaction system after completing step S3, and the polymerization reaction continues to form a random copolymer shell on the outside of the hole transport polymer brush. S5. Hydrolysis and condensation to form a crosslinked protective layer: Add alkaline substances and water to the reaction solution obtained in step S4 to adjust the pH to alkaline, and perform hydrolysis and condensation treatment to cause the silane groups in the crosslinkable silane monomer to undergo hydrolysis and condensation, forming a three-dimensional crosslinked silica network. After post-processing, the surface-modified quantum dot material is obtained.
[0007] In a further embodiment, in step S1, the RAFT reagent is 4-cyano-4-(thiobenzoyl)valerate, whose molecular structure contains both a carboxyl group and a thiobenzoyl group. The carboxyl group is used for esterification with lipoic acid, and the thiobenzoyl group provides the active end group for RAFT polymerization. The esterification reaction uses N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine as catalysts, wherein N,N'-dicyclohexylcarbodiimide acts as a dehydrating agent to activate the carboxyl group, and 4-dimethylaminopyridine acts as an acylation catalyst, which can improve the reaction efficiency and product purity.
[0008] In a further embodiment, in step S2, the amount of LA-RAFT ligand added is 50 to 150 times the molar amount of quantum dots. If the amount added is less than 50 times, the ligand exchange is insufficient and the grafting density on the quantum dot surface is insufficient. If it is more than 150 times, it is easy to cause excessive physical adsorption of ligands, which is difficult to completely remove by washing. Preferably, it is 80 to 120 times. The ligand exchange reaction is carried out under nitrogen protection and stirred at 50 to 60°C for 1 to 3 hours.
[0009] In a further embodiment, in step S3, the hole transport monomer is N-vinylcarbazole, which has excellent hole migration ability and electrochemical stability. The polyN-vinylcarbazole brush formed after polymerization can effectively reduce the hole injection barrier. The free radical initiator is azobisisobutyronitrile, which has a moderate decomposition temperature (60-70℃) and is compatible with RAFT polymerization conditions. The RAFT polymerization reaction conditions are: reaction at 60-65℃ for 2-5 hours under a nitrogen atmosphere. Under these conditions, the polymerization process is controllable and the molecular weight distribution is narrow. The hole transport polymer brush is a polyN-vinylcarbazole brush with a thickness of 2-10 nm.
[0010] In a further embodiment, in step S4, the electron transport monomer is 2-(4-vinylphenyl)-5-phenyl-1,3,4-oxadiazole, which has high electron affinity and good electron transport performance, and can balance the carrier concentration in the quantum dot luminescent layer; the crosslinkable silane monomer is 3-(trimethoxysilyl)propyl acrylate, whose acrylate double bond can participate in free radical copolymerization, and the trimethoxysilyl group is used for subsequent hydrolysis and condensation to form a crosslinked network; the conditions for continuing the polymerization reaction are 60-65°C for 30-70 minutes.
[0011] In a further embodiment, in step S4, the molar ratio of the added electron transport monomer to the crosslinkable silane monomer is 1:1 to 1:3. This ratio range can balance electron transport performance and crosslinking density: when the ratio is close to 1:1, the proportion of electron transport units is relatively high, which is beneficial to carrier balance; when the ratio reaches 1:3, there are more silane units, and the subsequent crosslinked protective layer is denser and has better weather resistance. It can be adjusted within this range according to the actual device requirements.
[0012] In a further embodiment, in step S5, the alkaline substance is ammonia water, and the pH is adjusted to 8-8.5. This weakly alkaline condition can gently catalyze the hydrolysis and condensation of silane groups, avoiding the damage of strong alkali to the quantum dot core-shell structure or polymer brush. The hydrolysis and condensation treatment conditions are: stirring at 20-25°C for 12-15 hours.
[0013] In a further embodiment, step S5 includes post-treatment comprising centrifugation, washing, and vacuum drying, specifically for 10–15 minutes; washing is repeated 2–4 times using toluene, ethanol, or a mixture of both solvents to remove unreacted monomers, catalysts, and byproducts; vacuum drying is performed at 40–60°C for 12–24 hours to avoid damaging the organic functional layer at high temperatures.
[0014] In a further embodiment, the quantum dots in step S2 are core-shell structured quantum dots synthesized in the oil phase, including CdSe / ZnS, InP / ZnS, or perovskite quantum dots (such as CsPbX3, where X = Cl, Br, I). Among these, CdSe / ZnS quantum dots have high luminescence efficiency and good stability; InP / ZnS quantum dots do not contain heavy metals and are environmentally friendly.
[0015] In a further scheme, except for the centrifugation and washing operation in step S2, all other steps are carried out continuously in a single reaction vessel, and no intermediate product separation and purification is performed between steps S3, S4, and S5. This "one-pot" continuous reaction process significantly reduces the loss of quantum dots and the shedding of surface ligands caused by multiple centrifugations, washing, and drying. The overall yield is 20% to 40% higher than that of the stepwise purification method, and the preparation cycle is shortened by about 30% to 50%, making it more suitable for large-scale production. At the same time, the continuous solution environment is conducive to maintaining the dispersion stability of quantum dots and ensuring uniform polymer brush grafting.
[0016] Compared with the prior art, the present invention provides a method for preparing electroluminescent quantum dot surface modification materials, which has the following beneficial effects: 1. The preparation method of this electroluminescent quantum dot surface modification material adopts LA-RAFT functional ligands with thioctic acid disulfide ring dual anchoring structure and RAFT active end groups, and performs ligand exchange on quantum dots to achieve highly stable grafting of functionalized ligands on the quantum dot surface. The dual anchoring groups can significantly enhance the binding strength between the ligand and the quantum dot surface, effectively avoiding the problems of easy detachment of traditional monodentate ligands and unstable modification layer, and providing uniform and firm reaction sites for subsequent polymerization.
[0017] 2. The preparation method of the electroluminescent quantum dot surface modification material achieves bidirectional balanced transport of charge carriers on the quantum dot surface by stepwise grafting of hole transport blocks through RAFT controllable polymerization and in-situ copolymerization to introduce electron transport units. The hole transport layer and the electron transport units form a gradient matching structure, which can synergistically improve the efficiency of charge carrier injection, transport and recombination, reduce luminescence quenching, and significantly improve the electroluminescence efficiency and brightness of quantum dots.
[0018] 3. The preparation method of the electroluminescent quantum dot surface modification material is to introduce crosslinkable silane groups on the outside of the polymer brush and form a three-dimensional silica crosslinked network by hydrolysis and condensation under alkaline conditions, thereby realizing the construction of a dense inorganic-organic composite protective layer on the surface of the quantum dots. This crosslinked layer can effectively block water, oxygen, heat and impurity erosion, significantly improve the storage stability, working stability and weather resistance of quantum dots, and extend the service life of devices. Attached Figure Description
[0019] Figure 1 This is a flowchart illustrating the overall process of the method of the present invention. Figure 2 This is an overall flowchart of the method of the present invention; Figure 3 This is a flowchart of step S1 of the present invention; Figure 4 This is a flowchart of step S2 of the present invention; Figure 5 This is a flowchart of step S3 of the present invention; Figure 6 This is a flowchart of step S5 of the present invention. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art, and all materials, equipment, etc., used herein are commercially available.
[0022] Please see Figures 1-6 The present invention provides a technical solution: A method for preparing an electroluminescent quantum dot surface-modified material, comprising the following steps: S1. Synthesis of a bifunctional ligand with a bi-anchored, reversible addition-fragmentation chain transfer function: Lipoic acid was reacted with a carboxyl-containing RAFT reagent via esterification to prepare a bifunctional ligand containing a disulfide ring anchoring group of lipoic acid and an active end group for RAFT polymerization, denoted as LA-RAFT. The RAFT reagent was 4-cyano-4-(thiobenzoyl)valerate, whose molecular structure contained both a carboxyl group and a thiobenzoyl group. The carboxyl group was used for esterification with lipoic acid, and the thiobenzoyl group provided the active end group for RAFT polymerization. The esterification reaction was catalyzed by N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine. N,N'-dicyclohexylcarbodiimide acted as a dehydrating agent to activate the carboxyl group, and 4-dimethylaminopyridine acted as an acylation catalyst, which improved the reaction efficiency and product purity. S2. Ligand Exchange and RAFT Functionalization of Quantum Dot Surface: Oil-synthesized quantum dots are dispersed in an organic solvent, and the LA-RAFT ligands obtained in step S1 are added for a ligand exchange reaction. Unreacted ligands are removed by centrifugation and washing, yielding quantum dots grafted with LA-RAFT, denoted as QD-RAFT. The amount of LA-RAFT ligand added is 50–150 times the molar amount of the quantum dots. If the amount is less than 50 times, the ligand exchange is insufficient, and the grafting density on the quantum dot surface is inadequate; if it is more than 150 times, excessive ligand physical adsorption is likely to occur, making complete removal by washing difficult. A preferred amount is 80–120 times. Stirring at 50–60°C for 1–3 hours under nitrogen protection promotes ligand exchange kinetics while avoiding high temperatures that could lead to fluorescence quenching or aggregation of quantum dots. The quantum dots are core-shell structured quantum dots synthesized in the oil phase, including CdSe / ZnS, InP / ZnS, or perovskite quantum dots (such as CsPbX3, where X = Cl, Br, I). Among them, CdSe / ZnS quantum dots have high luminous efficiency and good stability; InP / ZnS quantum dots do not contain heavy metals and are environmentally friendly; perovskite quantum dots have a wide color gamut and excellent color purity. Different types of quantum dots can be selected according to the target luminous color and application scenario, and the surface modification method of this invention is applicable to all of them. S3. Controlled Polymerization Grafting of Hole Transport Blocks: The QD-RAFT obtained in step S2 is dispersed in a degassed solvent, and hole transport monomers and free radical initiators are added to carry out RAFT polymerization. Hole transport polymer brushes are grafted onto the quantum dot surface to obtain QD-polymer brushes. The hole transport monomer is N-vinylcarbazole, which has excellent hole migration ability and electrochemical stability. The poly-N-vinylcarbazole brush formed after polymerization can effectively reduce the hole injection barrier. The free radical initiator is azobisisobutyronitrile, which has a moderate decomposition temperature (60-70℃) and is compatible with the RAFT polymerization conditions. The RAFT polymerization reaction conditions are: reaction at 60-65℃ for 2-5 hours under a nitrogen atmosphere. Under these conditions, the polymerization process is controllable and the molecular weight distribution is narrow. The hole transport polymer brush is a poly-N-vinylcarbazole brush with a thickness of 2-10 nm. When the thickness is less than 2 nm, it is difficult to form a continuous hole transport channel. When the thickness is greater than 10 nm, it may increase the steric hindrance and affect the introduction of subsequent electron transport units. S4. In-situ copolymerization to introduce electron transport units and crosslinkable silane groups: Electron transport monomers and crosslinkable silane monomers are directly added to the reaction system after step S3, and the polymerization reaction continues. A random copolymer shell is formed on the outside of the hole transport polymer brush. The electron transport monomer is 2-(4-vinylphenyl)-5-phenyl-1,3,4-oxadiazole, which has high electron affinity and good electron transport performance, and can balance the carrier concentration in the quantum dot light-emitting layer. The crosslinkable silane monomer is 3-(trimethoxysilyl)propyl acrylate, whose acrylate double bonds can participate in free radical copolymerization, while the trimethoxysilyl group is used for subsequent hydrolysis and condensation to form a crosslinked network. The polymerization reaction continues at 60–65°C for 30–70 minutes. This shorter reaction time avoids excessive consumption of monomers and prevents chain transfer side reactions in the grafted polymer, thus forming a random copolymer shell of moderate thickness. The molar ratio of the added electron transport monomer to the crosslinkable silane monomer is 1:1 to 1:3. This ratio range can balance electron transport performance and crosslinking density: when the ratio is close to 1:1, the proportion of electron transport units is higher, which is beneficial to carrier balance; when the ratio reaches 1:3, there are more silane units, and the subsequent crosslinked protective layer is denser and has better weather resistance. This range can be adjusted according to the actual device requirements. S5. Hydrolysis and condensation to form a crosslinked protective layer: An alkaline substance and water are added to the reaction solution obtained in step S4 to adjust the pH to alkaline. Hydrolysis and condensation treatment is then performed to cause the silane groups in the crosslinkable silane monomers to undergo hydrolysis and condensation, forming a three-dimensional crosslinked silica network. After post-treatment, surface-modified quantum dot materials are obtained. The alkaline substance is ammonia water, and the pH is adjusted to 8-8.5. This weakly alkaline condition can gently catalyze the hydrolysis and condensation of the silane groups, avoiding the damage of strong alkali to the quantum dot core-shell structure or polymer brush. (Conditions for hydrolysis and condensation treatment are missing from the original text.) The process involves stirring at 20–25°C for 12–15 hours. Reacting at room temperature ensures a uniform and controllable crosslinking process; too short a time results in incomplete crosslinking, while too long a time may cause unnecessary side reactions or quantum dot precipitation. Post-treatment includes centrifugation, washing, and vacuum drying, specifically for 10–15 minutes. Washing is performed 2–4 times using toluene, ethanol, or a mixture of both solvents to remove unreacted monomers, catalysts, and byproducts. Vacuum drying is carried out at 40–60°C for 12–24 hours to avoid damaging the organic functional layer at high temperatures.
[0023] Furthermore, except for the centrifugation and washing operation in step S2, all other steps are carried out continuously in a single reaction vessel, and no intermediate product separation and purification are performed between steps S3, S4, and S5. This "one-pot" continuous reaction process significantly reduces the loss of quantum dots and the shedding of surface ligands caused by multiple centrifugations, washing, and drying. The overall yield is 20% to 40% higher than that of the stepwise purification method, and the preparation cycle is shortened by about 30% to 50%, making it more suitable for large-scale production. At the same time, the continuous solution environment is conducive to maintaining the dispersion stability of quantum dots and ensuring uniform polymer brush grafting.
[0024] Example 1 This embodiment provides a method for preparing electroluminescent quantum dot surface modification materials, specifically including the following steps: S1. Synthesis of the dual-anchored-reversible addition-fragmentation chain transfer functional ligand (LA-RAFT): In a dry three-necked flask, add 1.0 mmol of lipoic acid, 1.0 mmol of 4-cyano-4-(thiobenzoyl)valerate (RAFT reagent), 0.1 mmol of 4-dimethylaminopyridine (DMAP), and 20 mL of anhydrous dichloromethane. Add 1.1 mmol of N,N'-dicyclohexylcarbodiimide (DCC) under ice bath conditions. Stir at room temperature for 24 hours. After the reaction is complete, filter to remove dicyclohexylurea. Wash the filtrate successively with 0.1 M hydrochloric acid and saturated brine, dry with anhydrous magnesium sulfate, remove the solvent by rotary evaporation, and purify by column chromatography (eluent: petroleum ether / ethyl acetate = 4:1) to obtain a red solid, which is the LA-RAFT ligand. S2. Ligand exchange and RAFT functionalization of quantum dot surface: CdSe / ZnS core-shell quantum dots synthesized in the oil phase (emission peak at approximately 530 nm, molar concentration of 0.01 mmol) were dispersed in 5 mL of toluene, and 0.8 mmol (80 times the molar amount) of LA-RAFT ligand prepared in step S1 was added. The mixture was stirred at 55 °C for 2 hours under nitrogen protection. After the reaction was completed, excess ethanol was added, and the mixture was centrifuged (12000 rpm, 10 minutes) to precipitate the quantum dots. The mixture was then washed three times with a toluene / ethanol mixed solvent and dried under vacuum to obtain quantum dots grafted with LA-RAFT, denoted as QD-RAFT. S3. Controlled polymerization grafting of hole transport blocks: The QD-RAFT obtained in step S2 was dispersed in 5 mL of degassed toluene, and the hole transport monomer N-vinylcarbazole (2 mmol) and the free radical initiator azobisisobutyronitrile (AIBN, 0.01 mmol) were added. After three freeze-thaw deoxygenation cycles, the mixture was heated to 65 °C under a nitrogen atmosphere and reacted for 3 hours. After the reaction was completed, a sample was taken and the thickness of the poly-N-vinylcarbazole brush was measured to be approximately 5 nm, thus obtaining the QD-polymer brush. No intermediate product separation and purification was performed in this step. S4. In-situ copolymerization to introduce electron transport units and crosslinkable silane groups: 2-(4-vinylphenyl)-5-phenyl-1,3,4-oxadiazole (0.5 mmol) and 3-(trimethoxysilyl)propyl acrylate (0.5 mmol, molar ratio 1:1) are directly added to the reaction system after step S3. Polymerization is continued at 65°C under nitrogen protection for 50 minutes to form a random copolymer shell on the outside of the hole transport polymer brush. S5. Hydrolysis and condensation to form a cross-linked protective layer: Add 0.5 mL of ammonia (28% by mass) and 0.5 mL of deionized water to the reaction solution obtained in step S4, adjust the pH of the system to 8.2, and stir at 25 °C for 13 hours to form a three-dimensional cross-linked silica network of silane groups. After the reaction is completed, collect the product by centrifugation, wash it three times with ethanol, and dry it under vacuum to obtain the surface-modified quantum dot material.
[0025] Transmission electron microscopy (e.g.) Figure 6 As shown in the figure, the obtained quantum dots are uniformly dispersed, and a composite layer of uniform thickness (about 12-15 nm) is observed on the surface. Photoluminescence spectroscopy shows that, compared with unmodified quantum dots, the luminescence intensity retention rate of the product in the thin film state is increased to 92%, and the luminescence intensity decays by less than 8% after 24 hours of continuous ultraviolet irradiation, demonstrating excellent stability.
[0026] Example 2 This embodiment is basically the same as embodiment 1, except that: The quantum dots used in step S2 are InP / ZnS core-shell quantum dots; In step S2, the amount of LA-RAFT ligand added is 50 times the molar amount of quantum dots; In step S3, the polymerization reaction time was 2 hours, and the thickness of the polymer brush was measured to be approximately 2 nm. In step S4, the molar ratio of electron transport monomer to crosslinkable silane monomer is 1:2 (i.e., 0.4 mmol of electron transport monomer and 0.8 mmol of crosslinkable silane monomer are added), and the polymerization time is 30 minutes. In step S5, the pH is adjusted to 8.5 with ammonia and stirred at 20°C for 15 hours.
[0027] Tests showed that the fluorescence quantum yield (PLQY) of the obtained InP / ZnS-based surface-modified quantum dots remained above 85%. When used as the light-emitting layer to prepare QLED devices, the maximum external quantum efficiency (EQE) of the devices reached 12.5%, which is about 60% higher than that of unmodified quantum dot devices.
[0028] Example 3 This embodiment is basically the same as embodiment 1, except that: The quantum dots used in step S2 are CsPbBr3 perovskite quantum dots. In step S2, the amount of LA-RAFT ligand added is 150 times the molar amount of quantum dots, and the exchange reaction is carried out at 60°C for 1 hour. In step S3, the polymerization reaction time was 5 hours, and the thickness of the polymer brush was measured to be approximately 10 nm. In step S4, the polymerization reaction time is 70 minutes, and the molar ratio of electron transport monomer to crosslinkable silane monomer is 1:3 (0.25 mmol of electron transport monomer and 0.75 mmol of crosslinkable silane monomer). In step S5, adjust the pH to 8.0 and stir at 22°C for 12 hours.
[0029] Tests showed that the perovskite quantum dots, after the above surface modification, exhibited significantly improved dispersion stability in water and ethanol, with no obvious aggregation or precipitation within 60 days. The photoluminescence decay kinetics of the thin film showed that the non-radiative recombination pathway was effectively suppressed.
[0030] Example 4 This embodiment focuses on verifying the advantages of the "one-pot" continuous reaction. The steps are carried out exactly as in Example 1, but no centrifugation, washing or drying of intermediate products is performed between steps S3, S4 and S5. All of these steps are completed continuously in the same reaction vessel. As a comparison, a control example is set up: a centrifugation purification step is added after step S3 and before step S4.
[0031] The results showed that the polymer brush grafting density of the product obtained in Example 4 (one-pot method) was comparable to that of the stepwise purification method (control example), but the total yield (in terms of quantum dots) was increased by about 30%, and the preparation time was shortened by about 40%. Device performance tests showed that the EQE of the quantum dot material prepared by the one-pot method in QLED devices was slightly higher than that of the control example, which is presumably due to the avoidance of partial detachment of surface ligands that may have been caused by intermediate purification.
[0032] Comparative Example 1 (Single Anchored Ligand Comparison) This comparative example is basically the same as Example 1, but in step S1, lipoic acid is not used. Instead, a monothiol RAFT reagent (such as dodecyl trithiocarbonate) is used directly as the comparative ligand. The other steps are the same.
[0033] The results showed that during the RAFT polymerization process in step S3, some quantum dots aggregated and precipitated. After centrifugation and washing, the amount of polymer grafting on the surface of the final product was significantly lower than that in Example 1. In the QLED device, the maximum brightness of the quantum dots obtained in Comparative Example 1 was only 40% of that in Example 1, indicating that the binding strength of the single anchored ligand was insufficient and it was easy to fall off under polymerization conditions, resulting in a decrease in the modification effect.
[0034] Comparative Example 2 (without cross-linking protective layer) This comparative example is basically the same as Example 1, but the step of adding crosslinkable silane monomers in step S4 is omitted, that is, the silica crosslink network is not formed, and step S5 is also omitted.
[0035] The results showed that although the obtained quantum dots had a dual-function polymer brush for hole and electron transport, their fluorescence intensity decreased to 60% of the initial value after being placed in air for 7 days. In contrast, the product of Example 1 maintained more than 95% of the initial value under the same conditions, indicating that the three-dimensional cross-linked silica protective layer is crucial for improving the environmental stability of quantum dots.
[0036] In summary, referring to Tables 1 and 2 below, the preparation method of electroluminescent quantum dot surface modification material provided by the present invention effectively solves the problems of easy detachment of quantum dot ligands, carrier imbalance and poor stability by using dual-anchored RAFT ligands, stepwise controllable polymerization and in-situ crosslinking protective layer construction. Moreover, the process is compatible with one-pot continuous production and has significant prospects for industrial application.
[0037] Table 1. Comparison of key process parameters in each embodiment Table 2. Performance Comparison of Examples and Comparative Examples Note: "—" indicates that the data was not directly tested in this embodiment, or is not directly related to the main indicator.
[0038] The present invention has been described in detail above. However, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, any modifications or improvements that do not depart from the spirit of the present invention are within the scope of protection of the present invention.
Claims
1. A method for preparing an electroluminescent quantum dot surface modification material, characterized in that, Includes the following steps: S1. Synthesis of bifunctional ligands with bi-anchored-reversible addition-fragmentation chain transfer: A bifunctional ligand containing a disulfide ring anchoring group of lipoic acid and a RAFT polymerization active end group was prepared by esterification reaction of lipoic acid with a carboxyl-containing RAFT reagent, denoted as LA-RAFT. S2, Ligand exchange and RAFT functionalization of quantum dot surface: The quantum dots synthesized in oil phase are dispersed in an organic solvent, and the LA-RAFT ligands obtained in step S1 are added to carry out a ligand exchange reaction. After centrifugation and washing to remove unreacted ligands, quantum dots with LA-RAFT grafted on the surface are obtained, denoted as QD-RAFT. S3. Controlled polymerization grafting of hole transport blocks: The QD-RAFT obtained in step S2 is dispersed in a degassed solvent, hole transport monomers and free radical initiators are added, and RAFT polymerization reaction is carried out to graft hole transport polymer brushes onto the surface of quantum dots to obtain QD-polymer brushes. S4. In-situ copolymerization to introduce electron transport units and crosslinkable silane groups: Electron transport monomers and crosslinkable silane monomers are directly added to the reaction system after completing step S3, and the polymerization reaction continues to form a random copolymer shell on the outside of the hole transport polymer brush. S5. Hydrolysis and condensation to form a crosslinked protective layer: Add alkaline substances and water to the reaction solution obtained in step S4 to adjust the pH to alkaline, and perform hydrolysis and condensation treatment to cause the silane groups in the crosslinkable silane monomer to undergo hydrolysis and condensation, forming a three-dimensional crosslinked silica network. After post-processing, the surface-modified quantum dot material is obtained.
2. The method for preparing the electroluminescent quantum dot surface modification material according to claim 1, characterized in that: In step S1, the RAFT reagent is 4-cyano-4-(thiobenzoyl)valerate; the esterification reaction uses N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine as catalysts.
3. The method for preparing the electroluminescent quantum dot surface modification material according to claim 1, characterized in that: In step S2, the amount of LA-RAFT ligand added is 50 to 150 times the molar amount of quantum dots; the ligand exchange reaction is carried out under nitrogen protection at 50 to 60°C with stirring for 1 to 3 hours.
4. The method for preparing the electroluminescent quantum dot surface modification material according to claim 1, characterized in that: In step S3, the hole transport monomer is N-vinylcarbazole; the free radical initiator is azobisisobutyronitrile; the RAFT polymerization reaction conditions are: reaction at 60-65°C for 2-5 hours under a nitrogen atmosphere; the hole transport polymer brush is a poly-N-vinylcarbazole brush with a thickness of 2-10 nm.
5. The method for preparing the electroluminescent quantum dot surface modification material according to claim 1, characterized in that: In step S4, the electron transport monomer is 2-(4-vinylphenyl)-5-phenyl-1,3,4-oxadiazole; the crosslinkable silane monomer is 3-(trimethoxysilyl)propyl acrylate; and the conditions for continuing the polymerization reaction are 60-65°C for 30-70 minutes.
6. The method for preparing the electroluminescent quantum dot surface modification material according to claim 5, characterized in that: In step S4, the molar ratio of the added electron transport monomer to the crosslinkable silane monomer is 1:1 to 1:
3.
7. The method for preparing the electroluminescent quantum dot surface modification material according to claim 1, characterized in that: In step S5, the alkaline substance is ammonia water, and the pH is adjusted to 8-8.5; the conditions for the hydrolysis and condensation treatment are: stirring at 20-25°C for 12-15 hours.
8. The method for preparing the electroluminescent quantum dot surface modification material according to claim 1, characterized in that: In step S5, the post-processing includes centrifugation, washing, and vacuum drying.
9. The method for preparing the electroluminescent quantum dot surface modification material according to claim 1, characterized in that: The quantum dots in step S2 are core-shell structured quantum dots synthesized in the oil phase, including CdSe / ZnS, InP / ZnS, or perovskite quantum dots.
10. The method for preparing the electroluminescent quantum dot surface modification material according to any one of claims 1-9, characterized in that: Except for the centrifugation and washing operation in step S2, all other steps are carried out continuously in a single reaction vessel, and no separation or purification of intermediate products is performed between steps S3, S4, and S5.